Mild to moderate post-COVID-19 alters markers of lymphocyte activation, exhaustion, and immunometabolic responses that can be partially associated by physical activity level— an observational sub-analysis fit- COVID study - Silva, Bruna Spolador de Alencar; Pereira, Telmo; Minuzzi, Luciele Guerra; Padilha, Camila Souza; Figueiredo, Caique; Olean-Oliveira, Tiago; dos Santos, Ivete Vera Medeiros; von Ah Morano, Ana Elisa; Marchioto Júnior, Osmar; Ribeiro, José Procópio Jabur; Dos Santos, Vanessa Ribeiro; Seelaender, Marília; et al. (Frontiers in Immunology, 2023)
This study aimed to evaluate if physical activity is associated with systemic and cellular immunometabolic responses, in young adults after mild-to-moderate COVID-19 infection. Mild- to- moderate Post-COVID-19 patients (70.50±43.10 days of diagnosis; age: 29.4 (21.9– 34.9) years; BMI: 25.5 ± 4.3 Kg.m2 n=20) and healthy age-matched controls (age: 29.3 (21.2 – 32.6) years; BMI: 25.4 ± 4.7 Kg.m2; n=20) were evaluated. Physical activity levels (PAL), body composition, dietary habits, muscular and pulmonary function, mental health, sleep quality, metabolic parameters, immune phenotypic characterization, stimulated whole blood and PBMC culture (cytokine production), mRNA and mitochondrial respiration in PBMCs were evaluated. Post-COVID-19 group exhibited lower levels of moderate to vigorous physical activity (MVPA) (p=0.038), therefore all study comparisons were performed with adjustment for MVPA. Post-Covid-19 impacted the pulmonary function (FEV1, FEV1 %pred, FVC and FVC %pred) compared to the control (p adjusted by MVPA (p adj) <0.05). Post-COVID-19 exhibited lower levels of serum IL-6 (p adj <0.01), while showed higher serum IL-10, triglycerides, leptin, IgG, ACE activity, TNFRSF1A and PGE2 (p adj <0.05) compared to controls. Post-COVID-19 presented lower percentage of Treg cells (p adj=0.03) and alters markers of lymphocyte activation and exhaustion (lower CD28 expression in CD8+ T cells (p adj=0.014), while CD4+T cells showed higher PD1 expression (p adj=0.037)) compared to control group. Finally, Post COVID-19 presented increased LPS-stimulated whole blood IL-10 concentration (p adj<0.01). When exploring mitochondrial respiration and gene expression in PBMCs, we observed a higher LEAK state value (p adj <0.01), lower OXPHOS (Complex I) (p adj=0.04), and expression of the Rev-Erb-α clock mRNA after LPS stimulation in the Post-COVID-19 than control (p adj<0.01). Mainly, PAL was associated with changes in IL-10, triglycerides, and leptin in the plasma of post-COVID-19 patients. PAL also was associated with modulation of peripheral frequency of Treg cells, the expression of PD-1 in CD8+ T cells, although abrogated the statistical effect in the analysis of TNF-α and IL-6 production by LPS- and PMA-stimulated PBMC of post-COVID-19 patients. Young adults after mild-to-moderate SARS-CoV-2 infection appear to have lower physical activity levels, which can be associated with clinical and immunometabolic responses in a complex manner.